Deux regards sur l’œuvre de Jean-Pierre Péneau à travers ses archives - Diane Aymard; Daniel Siret (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
A pioneer of French architectural research, Jean-Pierre Péneau died on April 1, 2021. His personal archives were recently transferred to the Centre d’archives d’architecture contemporaine in Paris and constitute a valuable legacy for understanding the life and work of Jean-Pierre Péneau in his time. Following the tribute paid in April 2022 by the Académie d’Architecture, this article would like to contribute to the interpretation of these archives. We propose two examinations that constitute the two parts of the article. The first, covering his entire career, exposes the great diversity of Jean-Pierre Péneau’s interests and, in so doing, highlights his successive decenterings and what can be called the paradox of his reputation. The second part of the paper deals in detail with a little-known aspect of Jean-Pierre Péneau’s scientific career, his first thesis prepared at the École Pratique des Hautes Études in Paris and never defended.